USING THE NOTE EDITOR FINALE-2004 IN PRACTICE (Scientific journal of the Fergana State University, 2024)
This article analyzes the rational use of the capabilities of the Final-2003 music editor, the possibilities of achieving efficiency in music education, as well as a comparative analysis of this computer program with the capabilities of existing music editors. Among computer notation programs, Finale, developed by MakeMusic, occupies a leading position both in the opinion of experts and in the number of users.